2018
DOI: 10.1016/j.apsusc.2018.07.064
|View full text |Cite
|
Sign up to set email alerts
|

Different spectroscopic behavior of coupled and freestanding monolayer graphene deposited by CVD on Cu foil

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Besides that, the exposure of the active area of the Cu and its oxides is also important when modified by using the graphene [25]. In 2018, the scientists found that the oxidation of the Cu surface can decrease the coupling between the graphene and the metal and thus can obtain freestanding-like characteristics for graphene [26]. Here, the free-standing compounds of Cu/Cu 2 O/CuO with graphene modification was formed by two steps and then used for glucose detection.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, the exposure of the active area of the Cu and its oxides is also important when modified by using the graphene [25]. In 2018, the scientists found that the oxidation of the Cu surface can decrease the coupling between the graphene and the metal and thus can obtain freestanding-like characteristics for graphene [26]. Here, the free-standing compounds of Cu/Cu 2 O/CuO with graphene modification was formed by two steps and then used for glucose detection.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of graphene placed on a uniform dielectric substrate, differential contrast of the scanning electron microscopy (SEM) image of flakes with different thicknesses is attributed to a dependence of the electron emission on the local work function of the 2D material. , This dependency introduces a suppression effect of the SE emission, which is primarily controlled by the increase in the number of graphene layers, or a reconstructed moiré in the case of heterostructures . The electron microscopy (EM)-based techniques provide a high resolution that merits more attention to correlate nonelectron-based and lower resolution methods with SEM or transmission EM (TEM) acquired from the same sample location. Correlative characterization across multiple techniques bridges resolution gaps and explains the properties of a material on the basis of spatially resolved co-located spectroscopic signals with in-plane imaging. Additionally, EM can be used to examine 2D materials in the cross-sectional view using a focused ion beam (FIB) system to prepare site-specific lamella from 2D flakes. , To the best of our knowledge, correlation between SEM and cross-sectional TEM has not been applied previously to count and confirm the number of 2D layers determined from SEM image contrast. Correlation of SE emission from flakes with different thicknesses can be essential because the assumption that the highest SE emission occurs from a monolayer may not be correct. , Hence, correlative methods on the same flake can help determine the relation between SEM image contrast and the number of 2D layers.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy has been widely used for studying many kinds of systems, such as: semiconductors, polymeric gel, phthalocyanine films, carbon-based systems (graphene and nanotubes), biopolymers, biomimetic biological systems and so on [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%